2016
DOI: 10.5812/jjm.32163
|View full text |Cite
|
Sign up to set email alerts
|

Role of Enterotoxigenic Bacteroides fragilis in Children Less Than 5 Years of Age With Diarrhea in Tabriz, Iran

Abstract: BackgroundDiarrhea is the most frequent health problem among children in developing countries. Defining the etiology of acute diarrhea is critical to disease therapy and prevention. Some anaerobic bacteria such as Enterotoxigenic Bacteroides fragilis (ETBF) strains cause diarrheal disease by production of enterotoxin in children less than 5 years old.ObjectivesThis study aimed to evaluate the prevalence of ETBF among common bacteria and viruses causing diarrhea in children aged less than five years.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Narimani et al (2016) demonstrated that none of the B. fragilis isolates harbored bft gene as their isolates were obtained from healthy individuals in Tehran, Iran [32]. In a study recently conducted in the north-west of Iran, four ETBF isolates were recovered from diarrheal fecal samples of the 100 outpatient and hospitalized children under the age of 5 years [33]. A study by Zamani et al (2017) conducted in Tehran and aimed to provide evidence of association between B. fragilis and ulcerative colitis (UC) and non-in ammatory bowel disease (nIBD).…”
Section: Discussionmentioning
confidence: 99%
“…Narimani et al (2016) demonstrated that none of the B. fragilis isolates harbored bft gene as their isolates were obtained from healthy individuals in Tehran, Iran [32]. In a study recently conducted in the north-west of Iran, four ETBF isolates were recovered from diarrheal fecal samples of the 100 outpatient and hospitalized children under the age of 5 years [33]. A study by Zamani et al (2017) conducted in Tehran and aimed to provide evidence of association between B. fragilis and ulcerative colitis (UC) and non-in ammatory bowel disease (nIBD).…”
Section: Discussionmentioning
confidence: 99%
“…In the age range of 1-5, bft was found in 31 (39%) diarrheal and 31 (16%) control specimens, although there was no significant difference (P = 0.088) [26]. A study from Iran, without control specimens, used anaerobic culture methods of 100 diarrheal specimens only and reported a bft rate of 5.72% [27]. Ramamurthy et al conducted a case-control study in India and demonstrated an ETBF rate of 7.2% in each the 446 patient and 428 control specimens, with no statistical difference [28].…”
Section: Detection Of Enterotoxin (Bft) Genementioning
confidence: 99%